Association between nutritional risk based on the NRS-2002 test and hospital morbidity and mortality - G. Mercadal-Orfila (Nutrición Hospitalaria, 2012)
Objective: To analyse the relationship between the presence of malnutrition (MN), as measured by the NRS-2002 nutritional evaluation, and the rate of morbidity and mortality. Design: Cross-sectional study. Setting: Patients admitted to Mateu Orfila Hospital, the regional hospital for the island of Menorca, Spain. Subjects: 1,075 patients who were admitted to Mateu Orfila Hospital (Menorca) who had laboratory studies and a nutritional risk (NR) evaluation available were studied. Those who had a clinical suspicion of MN or those at risk were studied. Intervention: Demographic (age, gender) and clinical (current weight, normal weight, body mass index, weight loss, oral intake, presence of intestinal failure, fistula, renal failure, respiratory infection, urinary infection, hyperglycaemia, admission to the ICU, hospital stay, days of parenteral nutrition treatment and reason for admission) were collected during hospitalisation, as well as hospital mortality and mortality at 6 months following discharge. All underwent the NRS-2002 test. Results: The mean patient age was 67.9 years and 58.3% were men. 62% of patients met the criteria for manutrition according to the NRS-2002 test. A statistically significant association was seen between malnutrition according to the NRS-2002 and intestinal failure, fistula, renal failure, respiratory infection, hyperglycaemia, hospital mortality and mortality at 6 months. Conclusion: Malnutrition affects more than half of the patients who are admitted to a medium-long admission hospital and it is associated with increased morbidity and mortality. The results underscore the need to establish an update plan and preventative and therapeutic nutritional follow-up. These measures reduce the rate of avoidable complications and save the costs associated with them.